A Phenomenological Study of the Role of Store Mannequins on the Experienced Responses of Generation-Y Female Customers - Kobra Najafi; Kambiz Heidarzadeh Hanzaee; Mohsen Khounsiavash (‫مدیریت بازرگانی)
Objective In marketing, in particular clothing marketing, the visual tool of the mannequin plays an important role in attracting the customers’ attention as a part of the store window. The effect of mannequins on the customers’ evaluation of clothing is not known and no study has been conducted based on lived experience in Iran. Mannequins play a role in visualizing clothes on customers' bodies, and the evaluation of customers with different bodies likely varies from clothing. Accordingly, this study aims to employ a phenomenological approach in examining the impact of mannequins on the experienced responses of female customers belonging to Generation Y.